Kinerja Pelayanan Air Bersih Berbasis Masyarakat di Tugurejo Kota Semarang - Yuliani, Yani; Rahdriawan, Mardwi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
PDAM water service by only 50 % to 10 % for urban and rural, to accelerate the fulfillment of the need for clean water, need to involve the private sector and communities. This study aims to assess the performance of community-based water services in Tugurejo. Analysis of performance in terms of aspects operational, finance, administration and customer satisfactio. The method of research used is a mixture methods (mixed methods), which combines the methods, techniques of data collection, and quantitative and qualitative data analysis. The results of the performance evaluation study covers aspects operasioanl organizers, finance and administration assessed predicate 'good', and